Canary caper by Ron Roy; illustrated by John Steven Gurney - Roy, Ron; Gurney, John, ill (New York Random House, 1998)
Dink and his friends investigate why pets, like Mrs. Davis's canary, Mozart, are mysteriously disappearing all over town.
A Stepping Stone book.
Keywords: Pets-FictionLost and found possessions-Fiction; Mystery and detective stories